Fiesta Toolkit: Model-Driven Software Product Lines in Practice (2010)
Model-Driven Software Product Lines (MD-SPLs) are those product lines whose members are created by using models and model transformations as first-class artifacts. In this paper we present the Fiesta toolkit, a set of tools to assist product line architects and products designers when creating MD-SPLs. The main characteristic of our toolkit is that it facilitates the creation of fine-grained configurations of products, i.e. configurations at the level of each element in models that will be transformed into product line members. For that, the toolkit includes a set of tools for the creation of MD-SPL projects, feature models, constraint models, binding models, OCL-type expressions to validate binding models against constraint models, and decision models.